Extraction and encapuslation of bioactive compounds from carrots - Šeregelj Vanja N. (Acta Periodica Technologica, 2017)
Carrot is an important root vegetable rich in bioactive compounds like carotenoids and polyphenols with appreciable levels of several other functional components having significant health-promoting properties. Utilization of carotenoids is limited due to their instability. Encapsulation is one of the alternatives used to improve carotenoid stability. The objectives of this study were to optimize the extraction and encapsulation of carotenoids from carrot. Freeze-dried carrots were extracted by conventional solvent extraction (CSE) using four solvents, i.e. ethanol, acetone, ethyl acetate, and hexane. Although CSE using hexane and ethyl acetate resulted in highest carotenoid contents (18.27 and 15.73 mg β-carotene/100 g), acetone and ethanol at a solid to solvent ratio 1:10 w/v with slightly lower carotenoid contents (14.52 and 11.45 mg β-carotene/100 g) were chosen for further studies due to their higher food compatibility and higher polyphenol content (88.86 and 66.21 mg GAE/100 g) than with lower solid to solvent ratio (1:5 w/v). Ethanol and acetone carrot extracts were encapsulated using different carriers by a freeze-drying method in order to obtain the optimum encapsulate with the highest carotenoid encapsulation efficiency (EE). Encapsulation using the maltodextrin, whey and soy protein as a wall material yielded an EE of carotenoids ranging from 41.95% to 100%. The encapsulated β-carotene content was evaluated during two months of storage at ambient temperature under light and dark conditions. Generally, the retention of carotenoids was significantly higher in dark conditions, where maximum retention (65.94-87.32%) occurred in the samples encapsulated in maltodextrin and soy protein. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR 31044]